1998
DOI: 10.1083/jcb.140.2.391
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Dynein and Dynactin Are Required for the Transport of Microtubules into the Axon

Abstract: Previous work from our laboratory suggested that microtubules are released from the neuronal centrosome and then transported into the axon (Ahmad, F.J., and P.W. Baas. 1995. J. Cell Sci. 108: 2761–2769). In these studies, cultured sympathetic neurons were treated with nocodazole to depolymerize most of their microtubule polymer, rinsed free of the drug for a few minutes to permit a burst of microtubule assembly from the centrosome, and then exposed to nanomolar levels of vinblastine to suppress further microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
173
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(191 citation statements)
references
References 51 publications
17
173
0
1
Order By: Relevance
“…Additionally, the cells adopt a rounded morphology as soon as 8 h after transfection. This phenotype is consistent with reported dominant negative and knockdown studies of LIS1 pathway members (6,14,30,31). Notably, the cells expressing myc-C do not detach from the plate even after 72 h; thus, this effect is not likely to be a simple cell death response.…”
Section: Disrupting Cytlek1 Function Alters Cell Shape and Microtubulsupporting
confidence: 76%
See 2 more Smart Citations
“…Additionally, the cells adopt a rounded morphology as soon as 8 h after transfection. This phenotype is consistent with reported dominant negative and knockdown studies of LIS1 pathway members (6,14,30,31). Notably, the cells expressing myc-C do not detach from the plate even after 72 h; thus, this effect is not likely to be a simple cell death response.…”
Section: Disrupting Cytlek1 Function Alters Cell Shape and Microtubulsupporting
confidence: 76%
“…7 B and C), similar but less severe than that observed with expression of myc-C and representative of disruption of microtubule transport to the cell periphery. Because the LIS1 pathway is critical for this transport process, inhibition of the function of any member of the LIS1 pathway has consistently resulted in accumulation of microtubules around the nucleus (6,30,31). This result thus provides additional evidence that cytLEK1 expression is critical for LIS1 pathway function.…”
Section: Lek1 Knockdown Alters Microtubule Network Organizationsupporting
confidence: 57%
See 1 more Smart Citation
“…A combination of photobleaching and difference imaging in cultured nerve cells showed that a subset of MTs in axons move fast and asynchronously (Wang and Brown, 2002). Injection of recombinant dynamitin arrests the translocation of MTs from the cell body into the axon, implicating cytoplasmic dynein in the process (Ahmad et al, 1998). Depletion of cytoplasmic dynein by RNAi in cultured rat sympathetic neurons has confirmed that cytoplasmic dynein is a key player in the anterograde transport of MTs (He et al, 2005).…”
Section: Motor Proteinsmentioning
confidence: 86%
“…Another axonal MAP named collapsin response mediator protein-2 (CRMP-2) binds tubulin dimers and stimulates axon growth and branching in hippocampal neurons in culture (Fukata et al 2002). Finally, microtubule motors such as dynein actively transport microtubules along the length of the axon, are required for axon growth, and may contribute to the microtubule invasion of growth cones during elongation (Ahmad et al 1998). Together, these data support a role for active regulation of microtubule activity in the control of axon outgrowth.…”
Section: The Growth Cone: Motor and Clutch Of Axon Growthmentioning
confidence: 99%